A Sensorless Vector Control for Stand-Alone Photovoltaic Water Pumping Systesms - Vu, Hoang Phuong; Nguyen, Tung Lam (Old Journal, 2017)
Stand-alone photovoltaic (PV) water pumping system is very important in rural areas and islands, where it is difficult or even impossible to reach electrical supply systems. This paper presents a sensorless vector control of an inductor motor (IM) and a hybrid maximum power point tracking algorithm to improve dynamic and robustness of the centrifugal pump in the stand-alone PV water pumping system. Analysis, simulation and hardware in the loop (HIL) experimental results are provided to demostrate advanced features of this proposed system.